Seed germination and proline accumulation in rice (oryza sativa L.) as affected by salt concentrations - Momayezi, Mohammad Reza; Abdul Rahman, Zaharah; Musa, Mohamed Hanafi; Ismail, Mohd Razi (Universiti Putra Malaysia Press, 2009)
Plant cells accumulate praline as an osmoprotectant to conserve osmotic stability and prevent damage. However, the accumulation of proline may not be associated with tolerance to salinity. This study considered the influences of NaCl and Na2SO4 compositions, at different concentrations, on seed germination and accumulation of proline in eleven rice genotypes. Rice seeds were grown in petri dishes in the laboratory and treated with distilled water as a control and NaCl and Na2SO4 (1:1 molar concentration ratio) at 2.5, 5.0, 7.5 and 10 dS m-1 electrical conductivity for 14 days. The mean germination time (MGT) was positively affected by the increase in the concentration of salt. Conversely, there was a negative relationship between germination index (GI) and salt concentration. Shirodi, Fajr, and Shafag can be classified into salt tolerant group, while Tarom-e-Hashemi was identified as salt susceptible, based on MGT and GI. Slight changes were recorded within dry weight and water content of seedlings at different salt levels. The maximum accumulation of proline was observed at 5 dS m-1 salt concentration. No relationship was established between the accumulation of proline and the growth parameters.